Handbook of terminology : Volume 1 - Kockaert, Hendrik; Steurs, F. (Frieda) (John Benjamins Publishing Company, 2015)
In this Handbook of Terminology (HoT), the symbiosis of Terminology with Linguistics allows a matrue and multi-dimensional reflections on terminological phenomena, which will eventually generate future applications which have not bee ntested yet in natural language. The HoT aims at disseminating knowledge about terminology (management) and at providing easy access to a large range of topics, traditions, best practices, and methods to a broad audience: students, researchers, professionals and lecturers in Terminology, scholars and experts from other disciplines (among which linguistics, life sciences, metrology, chemistry, law studies, machine engineering, and actually any expert domain). In addition, the HoT addresses any of those with a professional or personal interest in (multilingual) terminology, translation, interpreting, localization, editing, etc., such as communication specialists, translators, scientists, editors, public servants, brand managers, engineers, (intercultural) organization specialists, and experts in any field.